Assessment of Postoperative Nurses' Interventions for the Patients with Laparoscopic Cholecystectomy at Baghdad Teaching Hospitals - Kadhim, alaa; Kadhim, Haleema (Iraqi National Journal of Nursing Specialties, 2014)
Objective: The study aimed to assess the postoperative nurses' intervention for the patients with laparoscopiccholecystectomy and to determine the relationship between Nurses' interventions and their demographiccharacteristics.Methodology: Quantitative design (a descriptive study) was started from 20th November 2012 up to 1stSeptember 2013. Non-probability (purposive sample) of (50) nurses, who were working in surgical wards, wereselected from Baghdad teaching hospitals (Baghdad Teaching Hospital, Digestives System and Liver TeachingHospital, AL-Kindy Teaching Hospital, and AL-Kadhimiyia Teaching Hospita). The data were collected throughthe use of a constructed questionnaire, which consisted of two parts; the first part includes the page ofdemographic data which contains (10) items and the second part which includes (5) domains in (46) subdomainof postoperative nurses' interventions for the patients with laparoscopic cholecystectomy, throughdirect observant approach by the mean of the designed interventions checklist, Reliability of the questionnairewas determined through a pilot study and the validity through a panel of (12) experts. Descriptive statisticalanalysis procedures (frequency, percentage, mean of score, Standard Deviation and Relative Sufficiency), andinferential statistical analysis procedures (Reliability Coefficient, contingency coefficient and chi- square test)were used for the data analysis under application of the statistical package of social science (SPSS) ver. (10.0).Results: The findings of the study indicated that there is a weak assessment of postoperative nurses'interventions for the patients with laparoscopic cholecystectomy at Baghdad teaching hospitals, and thefindings indicated that the most of study items responding of questionnaire were (84.78%) significantdifferences. There was no significant relationship between nurses' gender, age, years of experience and theirassessment, while there was significant relationship between the level of education, sharing in training sessionswhich established (by the hospital, by other hospitals, or by other institutions), duration of the training session,Number of training sessions and assessment of postoperative nurses' interventionsRecommendations: The study recommended that special training session, concerning all nurses' surgical wardsfor postoperative nursing interventions (Laparoscopic Cholecystectomy Patient) at inside or outside Iraq, andbooklets should be designated and presented to all nurses' surgical wards, in addition to increasing the numberof professional nurses' graduate from the colleges of nursing to the enrolled in surgical wards.